2014
DOI: 10.1371/journal.pone.0090120
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Proteomic and Transcriptomic Analysis on Sulfur Metabolism Pathways of Arabidopsis thaliana under Simulated Acid Rain

Abstract: With rapid economic development, most regions in southern China have suffered acid rain (AR) pollution. In our study, we analyzed the changes in sulfur metabolism in Arabidopsis under simulated AR stress which provide one of the first case studies, in which the systematic responses in sulfur metabolism were characterized by high-throughput methods at different levels including proteomic, genomic and physiological approaches. Generally, we found that all of the processes related to sulfur metabolism responded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 54 publications
2
19
0
Order By: Relevance
“…These proteins included sulfur dioxygenase, sulfite oxidase, adenylyl-sulfate reductase, and inositol polyphosphate 1phosphatase. Sulfur is an essential mineral element involved in fundamental processes such as electron transport, structure, and regulation (Flávia, Capaldi Priscila, Gratão André, Reis Lima, & Azevedo, 2015 (Bick & Leustek, 1998;Liu et al, 2014). The results regarding sulfur metabolism are consistent with the improvement of the AsA-glutathione cycle and Cys and Met metabolism (described in detail in the subsequent section on amino acid metabolism) and indicated that AMF inoculation significantly improved sulfur metabolism to provide substrates for ROS and amino acid metabolism and thus enhanced the alkali tolerance of the P. tenuiflora seedlings.…”
Section: Sulphur Metabolismsupporting
confidence: 72%
See 1 more Smart Citation
“…These proteins included sulfur dioxygenase, sulfite oxidase, adenylyl-sulfate reductase, and inositol polyphosphate 1phosphatase. Sulfur is an essential mineral element involved in fundamental processes such as electron transport, structure, and regulation (Flávia, Capaldi Priscila, Gratão André, Reis Lima, & Azevedo, 2015 (Bick & Leustek, 1998;Liu et al, 2014). The results regarding sulfur metabolism are consistent with the improvement of the AsA-glutathione cycle and Cys and Met metabolism (described in detail in the subsequent section on amino acid metabolism) and indicated that AMF inoculation significantly improved sulfur metabolism to provide substrates for ROS and amino acid metabolism and thus enhanced the alkali tolerance of the P. tenuiflora seedlings.…”
Section: Sulphur Metabolismsupporting
confidence: 72%
“…It is taken up as sulfate and then assimilated into sulfur‐containing compounds. The compounds are crucial for plant survival under abiotic stress, and they include elemental sulphur, hydrogen sulfide, glutathione, phytochelatins, sulfur‐rich proteins (containing high levels of amino acids such as cysteine [Cys] and methionine [Met]), and several secondary metabolites (Bick & Leustek, ; Liu et al, ). The results regarding sulfur metabolism are consistent with the improvement of the AsA‐glutathione cycle and Cys and Met metabolism (described in detail in the subsequent section on amino acid metabolism) and indicated that AMF inoculation significantly improved sulfur metabolism to provide substrates for ROS and amino acid metabolism and thus enhanced the alkali tolerance of the P. tenuiflora seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Their results [ 18 ] of RNA-sequence and qRT-PCR suggested that the regulatory genes of different secondary metabolites were downregulated by AR treatment in relation to control vs AR-stressed tomato plant ( Table 1 ). Similar to these results, Liu et al [ 127 ] observed that AR treatment changed the expression pattern of differential genes and also the genes associated with secondary metabolites in plants. To the contrary, the use of melatonin in AR-stressed plants caused upregulation of secondary gene expression in control vs melatonin-treated AR-stressed plants, and AR-stressed plants vs melatonin-treated AR-stressed plants ( Table 1 ) [ 18 ].…”
Section: Role Of Melatonin In Plants Under Acid Rain Stresssupporting
confidence: 72%
“…Although only a subset of the phloem RNA fraction was analysed, results regarding the regulatory function of miRNA-395 were substantiated in further studies employing Arabidopsis (Kawashima et al, 2009, 2011). Sulphate metabolism in response to acid rain conditions has been investigated, with high inputs of S under low pH conditions (Liu et al , 2014). Acid rain is an ecological and a health problem in many countries due to combustion of fossil fuels releasing SO 2 .…”
Section: Transcriptomics Of Arabidopsis With Respect To Sulphur Metabmentioning
confidence: 99%